Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppressions; thématiques

The art of feminism: images that shaped the fight for equality, 1857-2017 - Arakistain, Xabier; Balshaw, Maria; Gosling, Lucinda; Reckitt, Helena; Robinson, Hilary; Tobin, Amy; Reckitt, Helena; Gosling, Lucinda; Robinson, Hilary; Tobin, Amy; Balshaw, Maria; Arakistain, Xabier (Chronicle Books, 2018)
Featured artists include: Beyonce, Louise Bourgeois, Andrea Bowers, Judy Chicago, Vanessa German, Jenny Holzer, Frida Kahlo, Barbara Kruger, AnaMendieta, Sethembile Msezane, Zanele Muholi, Shirin Neshat, Pussy Riot.Since its inception, the women's movement has harnessed the power of the image to transmit its message. From the posters of the Suffrage Atelier, to the photographs of Carrie Mae Weems, this comprehensive survey traces the ways in which feminists have shaped art and visual culture from the mid-nineteenth to the twenty-first centuries. Featuring more than 350 works of art, illustration, photography, performance, graphic design, and publlic protest, this stunning volume showcases the vibrancy and daring of the feministaesthetic over the last 150 years.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; discours; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Huit ans au pouvoir : une tragédie américaine - Coates, Ta-Nehisi (Présence Africaine, 2018)
Dans cette collection d'essais Ta-Nehisi Coates fait retentir les échos tragiques du passé colonialiste américain, dans les événements actuels : l'élection sans précédent de Barack Obama, suivie d'un contrecoup haineux et de l'élection de Donald Trump. Il examine aussi le temps présent à la lumière d'évènements historiques comme la guerre de Sécession, ou de programmes politiques comme l'incarcération de masse, qui ont profondément marqué la société américaine. Contenu : Introduction. Du bon gouvernement noir -- I. Notes de la première année « Voici comment nous avons perdu face à l'homme blanc » -- II. Notes de la deuxième année Une jeune Américaine -- III. Notes de la troisième année Pourquoi est-ce que si peu de Noirs étudient la guerre de Sécession ? -- IV. Notes de la quatrième année L'héritage de Malcolm X -- V. Notes de la cinquième année La peur d'un président noir -- VI. Notes de la sixième année Comme un Français -- VII. Notes de la septième année La famille noire à l'âge de l'incarcération de masse -- VIII. Notes de la huitième année Mon président était noir -- Épilogue Le premier président blanc.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; amériques; approches et analyses; cours; discipline; discours dominant; his4333; his4443; histoire et politique; inégalités; obama; politique américaine; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; trump; violence coloniale; violences; violences raciales